Patient and family engagement in Alberta Health Services: Improving care delivery and research outcomes. Issue 2 (March 2018) - Singh, Sarah; Burns, Katharina Kovacs; Rees, Jennifer; Picklyk, Deanna; Spence, Jessica; Marlett, Nancy
Engaging patients and families in research and the design of quality improvement is an essential component of Patient and Family Centred Care (PFCC). Alberta Health Services (AHS) has been engaging patients and families to promote a cultural shift towards PFCC. The AHS trains patient and family advisors to share their experiences and encourages staff to work with advisors to co-design improvements in care. This article briefly describes the role and growth of patient and family advisors, advisory groups, and the participation of advisors in research initiatives through AHS' Strategic Clinical Networks TM . It also describes recent efforts to build AHS' patient and family engagement capacity by introducing standard patient engagement training, supporting the creation of the innovative Patient and Community Engagement Research internship program, and by developing tools to measure the impact of patient and advisors on AHS. And finally, this article provides key learnings for health leaders.